Edukasi Pemilahan Sampah Rumah Tangga di Dusun Pending, Desa Soronalan, Kec. Sawangan, Kab. Magelang, Jawa Tengah - Ramadhan, Ahmad Athif Wahyu; Rahmawati, Tiara; Azzahra, Clarissa Radhi Putri; Kamila, Salsabila Syifa; Purbowati, Wahyu Wulan Nur; Styowati, Salsabila Dian (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2025)
Community service through education by Community Service activity of Poltekkes Kemenkes Yogyakarta 2025 student in Dusun Pending is based on the phenomenon that most of the people of Dusun Pending do not understand the importance of waste management. This educational activity with the target of housewives aims to make the people of Dusun Pending understand the importance of waste sorting, types of waste, the impact of waste, the benefits of waste and correct waste management. The method used was in the form of test results using the SPSS application as well as teaching aids in the form of 3 types of sorting waste bins, namely organic, inorganic, and B3 waste, with the results obtained in the form of an increase in knowledge and attitude after education of 77.95% and 38.58%. So this education on waste sorting can be considered to be able to increase public understanding of waste.